2020
DOI: 10.1177/1533033820965574
|View full text |Cite
|
Sign up to set email alerts
|

Serum lncRNA TINCR Serve as a Novel Biomarker for Predicting the Prognosis in Triple-Negative Breast Cancer

Abstract: Background: Tissue differentiation-inducing non-protein coding RNA (TINCR) has been shown to play a crucial role in pathogenesis of various types of human cancer including breast cancer (BC). The purpose of this study was to determine the potential prognostic value of serum lncRNA TINCR in BC. Methods: Quantitative reverse transcription PCR (qRT-PCR) was performed to detect serum lncRNA TINCR levels in 72 triple-negative BC (TNBC) patients, 105 non-TNBC patients, 60 benign breast disease patients and 86 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Among the lncRNAs involved in the model, several of them were reported to be associated with tumor progression, such as lncRNA TINCR [ 43 45 ] and TUG1 [ 46 48 ]. A recent study revealed that serum lncRNA TINCR level was significantly increased in TNBC and correlated with clinical outcome [ 49 ]. Tang et al [ 50 ] reported that lncRNA TUG1 could act as a miR-197 sponge to enhance cisplatin sensitivity in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Among the lncRNAs involved in the model, several of them were reported to be associated with tumor progression, such as lncRNA TINCR [ 43 45 ] and TUG1 [ 46 48 ]. A recent study revealed that serum lncRNA TINCR level was significantly increased in TNBC and correlated with clinical outcome [ 49 ]. Tang et al [ 50 ] reported that lncRNA TUG1 could act as a miR-197 sponge to enhance cisplatin sensitivity in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the expression analysis performed in the serum samples from 72 TNBC, 105 non-TNBC, 60 benign breast disease patients and 86 healthy subjects evidenced that higher lncRNA TINCR levels are detectable in BC patients, especially in TNBC, compared to subjects without cancer [ 91 ]. High circulating TINCR was significantly correlated with clinicopathological features and with poor OS in TNBC.…”
Section: Circulating Non-coding Rnas As Biomarkers In Tnbcmentioning
confidence: 99%
“…On the other hand, changes in ncRNA expression after the therapy can be a valuable precursor of tumor recurrence. In the Table 2 we summarized the recent studies analyzing the utility of circulating ncRNAs for TNBC prediction and prognosis [57,70,[78][79][80][81][82][83][84].…”
Section: Circulating Ncrnas For Tnbc Prediction and Prognosismentioning
confidence: 99%
“…Data regarding the utility of lncRNAs for prediction and prognosis is still limited and only few papers have focused on this idea [70,[83][84][85]. Among the lncRNAs, the TINCR seems to be the most promising TNBC-related lncRNA, serving as a diagnostic and prognostic biomarker.…”
Section: Lncrnasmentioning
confidence: 99%